2017
DOI: 10.1016/j.biomaterials.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

PNIPAAm-co-Jeffamine® (PNJ) scaffolds as in vitro models for niche enrichment of glioblastoma stem-like cells

Abstract: Glioblastoma (GBM) is the most common adult primary brain tumor, and the 5-year survival rate is less than 5%. GBM malignancy is driven in part by a population of GBM stem-like cells (GSCs) that exhibit indefinite self-renewal capacity, multipotent differentiation, expression of neural stem cell markers, and resistance to conventional treatments. GSCs are enriched in specialized niche microenvironments that regulate stem phenotypes and support GSC radioresistance. Therefore, identifying GSC-niche interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 62 publications
(111 reference statements)
2
29
0
Order By: Relevance
“…The physical barriers provided by the HA hydrogels caused the GSCs to form smaller but uniform spheroids compared to the tumorspheres in the suspension culture. These observations are consistent with recent studies utilizing PNIPAAm-co-Jeffamine ® (PNJ), PNIPAAm-PEG, and PEGDA-alginate scaffolds (Heffernan et al, 2017;Li et al, 2016;Oh, Cha, Kang, & Kim, 2016) to study GSCs. Overall, our results indicated that HA hydrogels could serve as a valuable tool to study clonally expanded glioblastoma cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The physical barriers provided by the HA hydrogels caused the GSCs to form smaller but uniform spheroids compared to the tumorspheres in the suspension culture. These observations are consistent with recent studies utilizing PNIPAAm-co-Jeffamine ® (PNJ), PNIPAAm-PEG, and PEGDA-alginate scaffolds (Heffernan et al, 2017;Li et al, 2016;Oh, Cha, Kang, & Kim, 2016) to study GSCs. Overall, our results indicated that HA hydrogels could serve as a valuable tool to study clonally expanded glioblastoma cells.…”
Section: Discussionsupporting
confidence: 91%
“…This observation is consistent with previous results of more homogenous cell distribution throughout the poly(lactide‐co‐glycolide scaffolds obtained after increasing the initial seeding density of bone‐marrow‐derived cells (Holy, Shoichet, & Davies, ). Glioblastoma cells have been cultured as multicellular tumorspheres to maintain their stemness phenotype (Bez et al, ; Heffernan et al, ). However, the large size of tumorspheres resulted in limited diffusion of nutrients and signaling factors essential for the maintenance of stem characteristics, and thereby, poor stem‐like population (Beier et al, ; Pollard et al, ; Woolard & Fine, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Javan and coworkers [41] introduced a jeffamine chemical functionalization in hyaluronic acid-based hydrogels to formulate a prolonged and sustained drug release and reduce the number of hydrogel injections: in vivo studies showed the efficiency of this material thanks to the improved biocompatibility and no signal of cell viability reduction. Similar biocompatibility aims were achieved in other works: the jeffamine was used as monomer to preserve some physico-mechanical properties, blood compatibility and cargo release [42][43][44][45], as copolymer with acrylamides derivatives to design 3D scaffolds able to modulate the lower critical solution temperature (LCST) and internalize cells [46] or as cross-linker to satisfy the no-cytotoxicity criteria [47]. However, the evaluation of the polymer antimicrobial features and the design of a 3D scaffold able to preserve them is not widely investigated.…”
Section: The Role Of the Physico-chemical Transitionmentioning
confidence: 79%
“…,Florczyk et al (2016),and Oh et al (2016) Poly(N-isopropylacrylamide)Heffernan et al (2016Heffernan et al ( , 2017, andLi et al (2016) PolyacrylamideUlrich et al (2009),Pathak and Kumar (2012),Ruiz-Ontañon et al (2013),Fernandez-Fuente et al (2014),,Umesh et al (2014),Wong et al (2015), andGrundy et al (2016) PolycaprolactoneRao et al (2013a),Jain et al (2014),Kievit et al (2014Kievit et al ( , 2016, andCha et al (2016) PolystyreneKievit et al (2014) andMa et al (2016a) Poly(lactic acid)Ma et al (2012) Bioactive peptide/proteinTamaki et al (1997),Cordes et al (2003),Sarkar et al (2006),Ulrich et al (2009), Ananthanarayanan et al (2011), Pathak and Kumar (2012), Ruiz-Ontañon et al (2013), Jain et al (2014), Kim and Kumar (2014), Rape and Kumar (2014), Umesh et al (2014), Wang et al (2014), Rape et al (2015), Wong et al (2015), Heffernan et al (2016), Ma et al (2016a), and Ngo and Harley (2017) Complex three-dimensional (3D) models Ma et al (2012), Pathak and Kumar (2012), Rao et al (2013a), Jain et al (2014), Herrera-Perez et al (2015), Pedron et al (2015), Rape et al (2015), Cha et al (2016), Fan et al (2016), Li et al (2016), and Chonan et al (2017) BiOPHYSiCAL PROPeRTieS Stiffness Kim et al (2008), Ulrich et al (2009, 2010), Yang et al (2010), Ananthanarayanan et al (2011), Pathak and Kumar (2012), Florczyk et al (2013, 2016), Pedron and Harley (2013), Pedron et al (2013, 2015), Rao et al (2013a,b), Fernandez-Fuente et al (2014), Heffernan et al (2014, 2016, 2017), Kim and Kumar (2014), Rape and Kumar (2014), Umesh et al (2014), Wang et al (2014), Herrera-Perez et al (2015), Rape et al (2015), Wong et al (2015), Cha et al (2016), Grundy et al (2016), Chen et al (2017), and Ngo and Harley (2017) Porosity Kim et al (2008), Yang et al (2010, 2014), Ananthanarayanan et al (2011), Ma et al (2012, 2016a), Pathak and Kumar (2012), Florczyk et al (2013, 2016), Pedron and Harley (2013), Rao et al (2013a,b), Kievit et al (2014, 2016), Wang et al (2014, 2016), Herrera-Perez et al (2015), Cha et al (2016), Fan et al (2016), and Oh et al (2016) Microchannels Pathak and Kumar (2012), Pedron et al (2015), Fan et al (2016), and Chonan et al (2017) Fibers/alignment Kim et al (2008), Ulrich et al (2010), Yang et al (2010), Rao et al (2013a,b), Jain et al (2014), Herrera-Perez et al (2015), Cha...…”
mentioning
confidence: 99%